2017
DOI: 10.1055/s-0036-1588685
|View full text |Cite
|
Sign up to set email alerts
|

Donor–Acceptor Molecular Triangles

Abstract: The synthesis and optoelectronic properties of five donoracceptor molecules, featuring an electron-acceptor unit made of six fused benzenoid rings that resembles an equilateral triangle, are described. These molecular 'triangles' were synthesized in eight steps from simple building blocks such that the electron-donor substituents could be installed in the last step by means of the Suzuki cross-coupling reaction. All molecules absorb and emit visible light in the region of around 450-650 and 550-850 nm, respect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…We showed that the tri- tert -butyl derivative of 2 can easily be converted into donor–acceptor dyads with rare layered solid-state packing motifs. 7 Finally, because of the extra stabilization provided by the peripheral oxygen atoms, the doubly reduced conjugate base of 2 was the first TOT derivative with a triplet ground state detected by EPR spectroscopy. 8…”
mentioning
confidence: 99%
“…We showed that the tri- tert -butyl derivative of 2 can easily be converted into donor–acceptor dyads with rare layered solid-state packing motifs. 7 Finally, because of the extra stabilization provided by the peripheral oxygen atoms, the doubly reduced conjugate base of 2 was the first TOT derivative with a triplet ground state detected by EPR spectroscopy. 8…”
mentioning
confidence: 99%
“…10 Recently, several efficient methods for synthesizing TOT precursors were reported, however, further chemical modifications of the neutral radicals were not investigated. 11,12 In this study, we have newly synthesized TOT derivatives 1e and 1f having isopropyl and n-butyl groups, respectively, and investigated the steric effect of substituent groups on the π-stacking ability. The isopropyl group is sterically smaller than the tert-butyl group, and the n-butyl group is linear and more flexible.…”
mentioning
confidence: 99%